BAGAIMANA BAGAIMANA ENVIRONMENTAL COST, INTELLECTUAL CAPITAL DAN DEWAN DIREKSI MENINGKATKAN KINERJA KEUANGAN INDEKS LQ45 - Desy Agnesri Rezki Br Panggabean (Jurnal Akuntansi, Manajemen dan Ekonomi, 2019)
This study aims to analyze the influence of Environmental Cost, Intellectual Capital, and Board Of Director On Corporate Performance (Study Of Non Financial Companies Listed On The LQ45 Indeks Period 2014-2018). Sampling in this research is using a purposive sampling method. From this method, 8 mining LQ45 companies. The analytical model used si descriptive statistics, classic Assumption test, panel data regression analysis, simultaneous testing is proven by F test and partial testing with T-test. This research was conducted to see how the company's performance LQ45 during the year 2014-2018 seen from the ROA side, as well as the causal factor. This analysis can be beneficial in the morning user's financial statements especially stakeholders in taking business decisions. Environmental Cost is used to see how the company's responsibilities to the environment, Intellectual Capital to see how the company manages its intellectual property, and the board of directors is expected to make Effective. The results showed that: (1) Environmental cost has no significant effect on the company's performance. (2) Intellectual Capital has a significant effect on the company's performance. (3) The Board of Directors has no significant effect on the company's performance. (4) Environmental cost, Intellectual Capital, and board of directors simultaneously have a significant effect on the company's performance.